Pengaruh Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR) dan Non Performing Loan (NPL) terhadap Return On Asset (ROA) pada Bank Umum Milik Negara (BUMN) yang Terdaftar di Bursa Efek Indonesia (BEI) Periode 2017–2024 - Nur Hikmah Ramadhani; Noor Hidayati; Siti Rusidah; Novia Nour Halisa (Business Administration, FISIP ULM, 2025)
The impact of the Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), and Non-Performing Loans (NPL) on Return on Assets (ROA) in State-Owned Commercial Banks (BUMN) recorded on the Indonesia Stock Exchange (IDX) for the 2017–2024 Period.This inquiry is oriented to identifying and verifying the discrete and concurrent significance of CAR, LDR, and NPL in shaping the ROA performance of State-Owned Commercial Banks (SOEsz0 listed on the IDX throughout the specified period.The research subjects were all BUMN commercial banks registered on the IDX between 2017 and 2024, while the study population consisted of their complete financial reports for the same years. The sample size was 32 financial statements obtained from eight years of observation, multiplied by BRI, BNI, BTN, and Bank Mandiri, through a purposive sampling approach. Multiple linear regression was employed as the principal data-processing method. The research outputs indicate that CAR, LDR, and NPL exert statistically meaningful influences, both partially and simultaneously, on ROA.